Analysis of Physics Misconceptions of Students in Mechanic Materials Using the Tier Multiple Choice Diagnostic Test - Juliper Nainggolan; Bajongga Silaban; Dearlina Sinaga; Febriman Zendrato (AL-ISHLAH: Jurnal Pendidikan, 2023)
Misconception is a problem in physics education that affects both teachers and students and stops them from fully accomplishing their learning goals. It is a problem that haunts both teachers and students. The four-tiered test is a useful tool for determining the misconceptions that students have based on the reading of the literature. In spite of this, there are not a lot of diagnostic tests in the form of a four-tier test, one of which is on the topic of business and energy. The aim of this study is to examine the misconceptions held by students in class XI of the Senior High School in Medan regarding mechanics-related material. The study under consideration employs a descriptive qualitative research approach. The study involved a total of 377 student volunteers who were selected from six distinct educational institutions situated within the urban area of Medan. The present study employed a diagnostic test instrument comprising of 25 items and questionnaire sheets, utilising a multiple-choice format with four tiers. According to the findings, 9.1% of the students are able to comprehend the idea, 19.2% do not comprehend the idea, 26.2% are only partially comprehending, 41.4% were able to overcome their misconceptions, and 4.1% of the students could not be coded. Consequently, the level of students' misunderstandings of physics material related to mechanics at Senior High School in Medan falls into the medium category. After the conclusion of this study, a diagnostic test was created internally, employing a four-tier structure, specifically designed for assessing mechanical materials. As a result of this technological progress, instructors are now able to more easily identify and address students' misconceptions pertaining to the subject matter. This study can provide a basis for future research by serving as an initial stage of development.